Effect of salinity on emergence and on water stress and early seedling growth of sunflower and maize - Katerji N.; van Hoorn I.W.; Hamdy A.; Karam F.; Mastrorilli M. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
To study the effect of salinity on the emergence and early seedling growth of sunflower and maize, experiments were conducted in pots filled with sandy clay and sandy loam. The experiments consists of a control and four saline water qualities with chloride concentrations of 15, 30, 45, and 60 meq/l. The emergence of sunflower and maize were affected by salinity. Soil texture did not affect the emergence. During early seedling growth, salinity and soil texture affected the development of the seedlings that showed symptoms of water stress in the form of lower leaf water potential, stomatal conductance, and evapotranspiration. The higher the salinity, the lower the leaf area and the dry matter production. Leaf, stem, and root showed an almost similar growth reduction due to salinity. Seedlings on sandy loam were more affected by water stress than those on sandy clay.